Llaqtaqasa, a settlement of the Late Intermediate Period (1100- 1400 AD) located in the district of Concepción, Vilcas Huamán province (Ayacucho region) - Martinez Sulca, Winnie Celeste (2021)
In this article, we will present, in grosso modo, the Llaqtaqasa archaeological site in the district of Concepción, province of Vilcas Huamán. Within this site, we will describe the sectors comprising it, the surrounding architectural structures, and the movable archaeological materials found on the surface. By analyzing this data, we propose a building date during the Late Intermediate Period, in a strategic point made up of large pampa areas with water sources used for productive activities development.